ACNM: advance coupling network model sleep/awake mechanism for wireless sensor networks - Mohammad, Habibulla; S. Chandrasekhara Sastry, A (International Journal of Engineering and Technology, 2017)
Wireless Sensor Network (WSN) has attracted many researchers due to its abilities in monitoring remote locations. To gather physical data, such as temperature, humidity, and so on WSNs are utilized. To fulfill the strict constraints like energy consumption and network performance, ongoing wireless sensor networks requires efficient methodologies and practices. The major concern in wireless networks is how to conserve the nodes energy so that network lifespan can be prolonging significantly. The research work focuses on ACNM-DEC (Advance Coupling Network Model-Deterministic Energy-efficient Clustering) protocol i.e. enhancing DEC protocol with sleep awake(S-A) mechanism to utilize energy efficiently. The technique sleep-awake is implemented by simply coupling nodes which are at nearer to one another. The nodes which are paired will switch in two modes i.e. Idle (sleep) and busy (awake). Sleep/wake scheduling is an essential consideration in sensor network applications. Finding an optimal sleep/wake scheduling strategy that would minimize computation and communication overhead, be resilient to node failures, and provide high-quality data service is extremely challenging. In this paper, we present and compare several state-of-the-art algorithms and techniques that aim to address the sleep/wake scheduling issue, which are divided into distributed and centralized manners. The obtained results of the simulation prove that the lifespan of the communication model has been extended in terms of its performance, good energy utility and data transmission.